Parental involvement in robot-mediated intervention: a systematic review - Piccolo, Adriana; De Domenico, Carmela; Di Cara, Marcella; Settimo, Carmela; Corallo, Francesco; Leonardi, Simona; Impallomeni, Caterina; Tripodi, Emanuela; Quartarone, Angelo; Cucinotta, Francesca (Frontiers in Psychology, 2024)
Introduction: Over the years, the conceptual approach to pediatric rehabilitation has reevaluated the parent's role in the therapeutic process, considering parental involvement as a necessary condition for the effectiveness of the intervention. In the field of pediatric intervention, the therapeutic use of robots represents a growing clinical interest, but the feasibility and applicability of these tools in interventions including parents is unclear. This systematic review aims to investigate parental involvement in robot-mediated intervention (RMI) for children and adolescents in current literature.Our main goal is to analyze and summarize all the existing experiences to discuss and draw future research directions and implications for clinical practice.Method: After collecting 1,106 overall results, the studies selected were analyzed using thematic analysis. The literature review was conducted in accordance with the PRISMA guidelines by searching PubMed and Web of Science, until 7 February 2023. Studies that met the following inclusion criteria were included: (1) robot as a therapeutic-rehabilitation tool; (2) presence/involvement of parents/caregivers in child-robot therapeutic sessions.Results: A total of 10 articles were included. Extracted data included study design, participant characteristics, type of robot used, outcomes measures, aim and type of intervention. The results reveal that parental involvement in RMI could be feasible and useful in improving intervention efficacy; particularly, in improving the child's social communicative abilities and the caregiver's educational skills.Discussion: RMI intervention with parental participation could be a useful therapeutic strategy in the pediatric age. However, to date, few studies have investigated this specific topic, and the reported results may enhance future research to understand its effectiveness in specific areas of use.